2018
DOI: 10.1111/ijd.14212
|View full text |Cite
|
Sign up to set email alerts
|

Palpebral cutaneous melanomas: a review of 17 cases from a tertiary center

Abstract: Palpebral skin melanoma is associated with favorable clinical features, and it is correlated with better survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Therefore, recent studies have focused on the molecular mechanisms underlying melanoma progression and metastases as well as on novel strategies for early effective therapy, including immune checkpoint inhibitors. [24][25][26] However, how to successfully inhibit melanoma metastases remains a major barrier to be overcome. Recently, increasing evidence has revealed that MACF1 plays an essential role in various cellular processes, and is involved in the control of microtubule dynamics that relates with cell proliferation and migration, thereby suggesting that MACF1 function is an important for cellular motility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recent studies have focused on the molecular mechanisms underlying melanoma progression and metastases as well as on novel strategies for early effective therapy, including immune checkpoint inhibitors. [24][25][26] However, how to successfully inhibit melanoma metastases remains a major barrier to be overcome. Recently, increasing evidence has revealed that MACF1 plays an essential role in various cellular processes, and is involved in the control of microtubule dynamics that relates with cell proliferation and migration, thereby suggesting that MACF1 function is an important for cellular motility.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 28% of patients will develop recurrence at a new site [13], and roughly one third will have more than one episode of recurrence [3]. Similarly, despite complete excision of the lesion on histopathology, nearly one quarter (21–24%) of patients with EM go on to develop local recurrence [8, 11, 14].…”
Section: Introductionmentioning
confidence: 99%